Implementation of Drive-Through Testing for COVID-19 With Community Paramedics. (16th October 2022) - Constantine, S. Tyler; Callaway, David; Driscoll, Jeremy N.; Murphy, Stephanie
Abstract: Objective: In this manuscript, we discuss the implementation and deployment of mobile integrated health and community paramedicine (MIH/CP) testing sites to provide screening, testing, and community outreach during the first months of the 2019 coronavirus disease (COVID-19) pandemic in the metropolitan region of Charlotte, North Carolina. This program addresses the need for an agile testing strategy during the current pandemic. We disclose the number of patients evaluated as "persons under investigation" and the proportion with positive severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) results from these sites. We describe how the programs were applied to patient care and include considerations on how additional staffing, scalability, and flexibility of these services may be applied to future patient and health care crises. Methods: This is a descriptive report of the implementation of MIH/CP test sites in our health care system's early response to the COVID-19 pandemic in March 2020. Retrospective data on the number of patients and their associated demographics are reported here as raw data. No statistical analysis was performed. Results: Between March 15, 2020, and April 15, 2020, our 6 MIH/CP test sites evaluated 4342 patients. Of these, 401 patients (9.2%) had positive test results, 62.8% of whom were women. The estimated duration of each patient encounter under investigation was 3 to 5 minutes. The paramedics were able to perform a brief history, specific physical examination, and screening for signs of hypoxemic respiratory failure. There were no cases of accidental exposure or failure of personal protective equipment for the MIH/CP paramedics. Conclusions: In our health care system, we pivoted the traditional MIH/CP model to rapidly initiate remote drive-through testing for COVID-19 in pre-screened individuals. This model allowed us to test patients with suspected COVID-19 patients away from traditional health care sites and mitigate exposure to health care workers and other patients.